Strategi Kesantunan Berbahasa Netizen dalam Menanggapi Kasus Joki UTBK oleh Mahasiswa Kedokteran di Tiktok: Kajian Pragmatik - Amanda, Amanda; Nurhalisah Rahman; Intan Meliasari; Anita Candra Dewi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
Abstrac: This study examines the language politeness strategies of netizens in the TikTok comment section responding to the UTBK jockey case by medical students using a pragmatic approach. Using descriptive qualitative method, the study analyzed the top 15 comments from the viral video based on Leech's politeness theory. The results show a variety of politeness strategies as some netizens apply the maxims of sympathy and generosity in providing support by considering economic factors and the future of the perpetrator, while violations of the maxims of tact and respect occur when expressing disapproval. The context of the situation plays a significant role in influencing the use of politeness maxims, especially on issues that touch on moral values and social justice. These findings indicate that TikTok is not just a means to find entertainment but also a discursive space where language politeness becomes an indicator of the ethical position and moral judgment of digital society.